Pengaruh Relaksasi Autonomous Sensory Meridian Response (Asmr)terhadap Tingkat Kecemasan Mahasiswa dalam Menghadapi Skripsi pada Mahasiswa Keperawatan Reguler Tingkat Akhir di Universitas Indonesia Maju Jakarta Tahun 2023 - Wili Suciani Wahono; Marisca Agustina; Nurul Ainul Shifa (Pusat Riset dan Inovasi Nasional, 2023)
Background: Students who are writing their theses experience several psychological disorders, one of which is anxiety disorders. One suitable treatment for treating anxiety disorders is to carry out Autonomous Sensory Meridian Response relaxation or commonly known as (ASMR). Watching ASMR videos can make students who feel anxious become calmer and more relaxed so that they can reduce their anxiety level and can complete their thesis according to the desired time. Objective: This research is to determine the effect of Autonomous Sensory Meridian Response (ASMR) relaxation on students' anxiety levels in facing a thesis for final year regular nursing students at the University of Indonesia Maju in 2023. Method: This research uses a quantitative research design with a one-group pre-test design approach before the treatment is given and a post-test after the treatment is given. Results: The majority of respondents are women (86.7%) and the majority of respondents were aged 21-22 years (86.7%). The majority of respondents before being given the intervention were in the mild anxiety category (46.7%) and the majority of respondents after being given the intervention were in the no anxiety category (73.3%). The Wilcoxon test result was p = 0.001 < 0.05, which means HA was accepted. Conclusion: There is an influence of Autonomous Sensory Meridian Response (ASMR) relaxation on final year regular nursing students in preparing their thesis at the Advanced Indonesia University.